Perlindungan Hukum Terhadap Pengguna Aplikasi E-Wallet Dana - Hartanto Hartanto; Vincent Rosadi; Ervin Alvaro Yosmar (Pattimura Legal Journal)
Introduction: It is becoming easier for people to use the internet, which previously had to be done in an internet cafe, but now it is quite practical to use a smartphone/Android. This opportunity is attractive for funding application service providers to develop their business in various ways. The impact is that people's hedonism as consumers increases while the risk of problems increases.